Anti-Streptococcus mutans and anti-biofilm activities of dextranase and its encapsulation in alginate beads for application in toothpaste - Juntarachot,Nucharee; Sirilun,Sasithorn; Kantachote,Duangporn; Sittiprapaporn,Phakkharawat; Tongpong,Piyachat; Peerajan,Sartjin; Chaiyasut,Chaiyavat (PeerJ, 2020)
Background The accumulation of plaque causes oral diseases. Dental plaque is formed on teeth surfaces by oral bacterial pathogens, particularly Streptococcus mutans, in the oral cavity. Dextranase is one of the enzymes involved in antiplaque accumulation as it can prevent dental caries by the degradation of dextran, which is a component of plaque biofilm. This led to the idea of creating toothpaste containing dextranase for preventing oral diseases. However, the dextranase enzyme must be stable in the product; therefore, encapsulation is an attractive way to increase the stability of this enzyme. Methods The activity of food-grade fungal dextranase was measured on the basis of increasing ratio of reducing sugar concentration, determined by the reaction with 3, 5-dinitrosalicylic acid reagent. The efficiency of the dextranase enzyme was investigated based on its minimal inhibitory concentration (MIC) against biofilm formation by S. mutans ATCC 25175. Box-Behnken design (BBD) was used to study the three factors affecting encapsulation: pH, calcium chloride concentration, and sodium alginate concentration. Encapsulation efficiency (% EE) and the activity of dextranase enzyme trapped in alginate beads were determined. Then, the encapsulated dextranase in alginate beads was added to toothpaste base, and the stability of the enzyme was examined. Finally, sensory test and safety evaluation of toothpaste containing encapsulated dextranase were done. Results The highest activity of the dextranase enzyme was 4401.71 unit/g at a pH of 6 and 37 °C. The dextranase at its MIC (4.5 unit/g) showed strong inhibition against the growth of S. mutans. This enzyme at 1/2 MIC also showed a remarkable decrease in biofilm formation by S. mutans. The most effective condition of dextranase encapsulation was at a pH of 7, 20% w/v calcium chloride and 0.85% w/v sodium alginate. Toothpaste containing encapsulated dextranase alginate beads produced under suitable condition was stable after 3 months of storage, while the sensory test of the product was accepted at level 3 (like slightly), and it was safe. Conclusion This research achieved an alternative health product for oral care by formulating toothpaste with dextranase encapsulated in effective alginate beads to act against cariogenic bacteria, like S. mutants, by preventing dental plaque.
Keywords: Streptococcus mutans; Dextranase; Encapsulation; Oral care; Toothpaste; Cariogenic bacteria